Konsekwencje ciągłego doskonalenia procesów w organizacjach - Brajer-Marczak, Renata (Consequences of Continuous Processes Improvement, 2009)
Currently continuous improvement of processes is becoming the challenge for the whole organization. This need is driven by cost competition and a pressure of quality improvement. There are various criterions and methods that can be pointed out. In the paper, the author focuses on presenting both, benefits of the processes and potential dangers or negative outcomes, as well. The author shows organizational, social, and economic consequences. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 153-161